Pengaruh Penggunaan Simulasi Virtual Laboratorium PhET (Physics Education Technology) Terhadap Hasil Belajar Siswa Pada Materi Geometri Molekul di MAN 1 Bitung - Puja Ika Abrianingsih Ritonga; Dokri Gumolung (Chemistry Department, Universitas Negeri Manado, 2021)
This research to see the side-effect of using virtual simulation media PhET (Physics Education Technology) laboratory on student learning towards in molecular geometry at MAN 1 Bitung. PhET is a form of virtual laboratory simulation with observation or experimental activities using software conducted by a computer or mobile phone. This research was a Pretest-Postest Control Group design with a 10th grade Mathematics and Natural Sciences students which is divided two groups they are, the control group and experimental group of 15 students each. The tests carried out to prove the hypothesis were carried out by t-test with the results of ttable = 2.04 and the value of tcount = 2.59. In this case tcount > ttable then, H1 accepted i.e. the average value of the experimental group learning result, morehigher than the control group. The results showed that, the PhET virtual laboratory simulation has a side-effect to students learning results. to measuring how much the side-effect is that, the result of simple with the results of the regression equation is regression had also won three other that is Y=0.6542x 27.26 that indicates who had a positive effect with a correlation as 0.72 correlation in the rate of the strong relationship and value of the coefficient of determination as much as 0,521 or Influental as much as 52,1℅.